Hubungan Invasi Pembuluh Limfe Dengan Metastasis ke Kelenjar Getah Bening Pelvis pada Kanker Serviks Stadium IB dan IIA - MANUEL HUTAPEA; SUHATNO -; DYAH FAUZIAH (Indonesian Journal of Cancer, 2014)
Objective: to know the result of Hematoxyllin-eosin and immunostainning D2-40 Podoplanin examination in detecting lymph vessel invasion (LVI) and to analyze correlation between lymph vessel invasion with pelvic lymph node metastasis in stage IB and IIA cervical cancer. Design of this research was cross-sectional study. The clinicopathological data of 41 patients with stage IB and IIA cervical cancer who underwent radical hysterectomy and pelvic lymphadenectomy (RHPL) at Dr. Soetomo Hospital, Surabaya, from January 2008 to June 2013 were retrospectively reviewed. Age, histology type, clinical stage, tumor size, number of removed pelvic lymph node, parametrial invasion and LVI were analyzed to define their correlation with pelvic node metastases. Immunohistochemical staining using MAb-D2-40 Podoplanin was used to detect lymph vessel invasion on the corresponding HE slides. Eligible criteria are paraffin wax embedded tissue from cervix cancer patients was diagnosed as cervix cancer, and patients medical record can be found and filled completely. Ineligible criteria are patients which is had chemotherapy or radiotherapy before surgery or patients paraffin wax embedded tissue was damaged. The correlation among variables was analyzed using Phi correlation test. Results: among of total 41 patients , lymph vessel invasion (LVI) was detected in 7 (17.07%) D2-40 Podoplanin slides, and 9 (21.95%) HE slides. Agreement rate with Kappa statistic between two method was significant, k = 0,381, p = 0,014. Lymph node metastasis was found in 6 (14.63%) samples. Positive LVI detected by D2-40 Podoplanin was significantly correlated with lymph node metastasis (? = 0.362; p = 0.02), but positive LVI detected by HE was not significantly correlated (? = 0.281; p = 0.072).